Internal Factors Affecting Commercial Bank Lending: Symmetric and Asymmetric Effects of Macro-Level Data Evidence - Arintoko, Arintoko (Jurnal Keuangan dan Perbankan, 2021)
The purpose of this study is to estimate the symmetric and asymmetric effects of internal factors on bank lending measured by loan to deposit ratio (LDR). The analysis model applies the Autoregressive Distributed Lag (ARDL) and nonlinear ARDL models. The data analyzed are monthly time series and cover the period of 2012M01 – 2020M06. The contribution of this research is the provision of empirical evidence of the asymmetric effect of internal bank performance on bank lending at the macro-level data. The results show that the non-performing loan (NPL) is a consistent and robust variable that has a negative effect on bank lending both in the short and long run, both symmetrically and asymmetrically. The capital adequacy ratio (CAR) positively affects bank lending when it decreases in the long run. Operating expense to operating income (OEOI) has a negative effect only in the short run, assuming symmetric and asymmetric effects. The liquid assets ratio (LAR) has a negative effect on bank lending when it increases both in the short and long run. The banking supervisory agency needs to consistently supervise and enforce regulations effectively related to bank soundness, especially those concerning increasing performing loans, strengthening the capital structure, and improving efficiency.DOI: 10.26905/jkdp.v25i3.5760